Cryptic species of Aspergillus section Terrei display essential physiological features to cause infection and are similar in their virulence potential in Galleria mellonella. Issue 1 (1st January 2019) - Lackner, Michaela; Obermair, Judith; Naschberger, Verena; Raschbichler, Lisa-Maria; Kandelbauer, Carmen; Pallua, Johannes; Metzlaff, Julia; Furxer, Sibylle; Lass-Flörl, Cornelia; Binder, Ulrike
ABSTRACT: Aspergillus species account for the majority of invasive mold infections in immunocompromised patients. Most commonly, members of the Aspergillus section Fumigati are isolated from clinical material, followed by isolates belonging to section Terrei . The section Terrei contains 16 accepted species. Six species were found to be of clinical relevance and studied for differences in growth adaptability and virulence potential. Therefore, a set of 73 isolates (22 A. terreus s.s., 8 A. alabamensis, 27 A. citrinoterreus, 2 A. floccosus, 13 A. hortai, and 1 A. neoafricanus ) was studied to determine differences in (a) germination kinetics, (b) temperature tolerance, (c) oxygen stress tolerance (1% O2 ), and (d) a combination of the latter two. Virulence potential of phialidic (PC) and accessory conidia (AC) was studied in G. mellonella larvae, using survival as read out. Further, the formation of AC was evaluated in larval tissue. All isolates were able to grow at elevated temperature and hypoxia, with highest growth and germination rates at 37°C. A. terreus s.s., A. citrinoterreus, and A. hortai exhibited highest growth rates. Virulence potential in larvae was inoculum and temperature dependent. All species except A. floccosus formed AC and germination kinetics of AC was variable. Significantly higher virulence potential of AC was found for one A. hortai isolate. AC could be detected in larval tissue 96 h post infection. Based on these findings, cryptic species of section Terrei are well adapted to the host environment and have similar potential to cause infections.